2014
DOI: 10.1007/s10517-014-2562-5
|View full text |Cite
|
Sign up to set email alerts
|

Noopept Normalizes Parameters of the Incretin System in Rats with Experimental Diabetes

Abstract: Experiments on adult Wistar rats with streptozotocin-induced diabetes showed that antihyperglycemic activity of an original nootropic and neuroprotective drug Noopept (N-phenylacetyl-L-prolylglycine ethyl ester) is more pronounced under conditions of oral application than after intraperitoneal injection. These data provided a basis for studying the effect of Noopept on major indexes of the incretin system. Streptozotocin was shown to decrease the concentrations of incretin GLP-1 and insulin in the blood. Noope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Exenatide treatment upregulated GLP-1 receptor gene expression as 2.010 fold changes. Our results confirm previous data [17,45] and might explain the protective role of exenatide in enhancing insulin secretion. So as it is suggested by During et al…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Exenatide treatment upregulated GLP-1 receptor gene expression as 2.010 fold changes. Our results confirm previous data [17,45] and might explain the protective role of exenatide in enhancing insulin secretion. So as it is suggested by During et al…”
Section: Discussionsupporting
confidence: 93%
“…The content of GLP‐1 decreases multiple folds in STZ‐receiving rats . In our study, hippocampal gene expression of GLP‐1 receptor downregulated as 4503 fold change in type 2 diabetic mice as compared to control group.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Although there are considerable studies on the anti-inflammatory effect of Noopept [28,61], the current study stated the novel dipeptide anti-hyperalgesic and anti-inflammatory effects were mediated via inhibition of microglia activity and apoptosis. Ostrovskaya et al showed that Noopept, through normalizing incretin system parameters, had an anti-apoptotic effect on pancreatic β cells in the context of experimental Diabetes [63], and in another study they indicated neuroprotective effects [64]. Moreover, the effects reported in this paper in response to Noopept were significantly more effective than those reported for minocycline administration in the CFA-inflamed groups, which indicates that there are other pathways involved in Noopept anti-inflammatory effects which need to…”
Section: Discussionmentioning
confidence: 50%